Caracterización estadística del desvanecimiento inducido por dispersión en sistemas de comunicación óptica inalámbrica submarina - Salcedo-Serrano, Pedro; Boluda-Ruiz, Rubén; Garrido-Balsells, José María; García-Zambrana, Antonio (My University, 2021)
An accurate underwater channel characterization is necessary for underwater optical wireless communication (UOWC) in order to improve its current limitations. This paper presents a new statistical model to characterize the scattering effect in terms of a fading never considered before by means of a Gamma distribution by using only one degree of freedom in clear ocean and coastal waters. The developed fading model is employed to compute the performance of UOWC systems in terms of bit error rate (BER) along with salinity-induced oceanic turbulence modeled by a Weibull distribution. The results demonstrate that the scattering-induced fading effect produces a strong performance degradation particularly in long link distances and, hence, it cannot be neglected when designing advanced communication systems. The analytical results are verified by Monte Carlo simulations.
Keywords: Comunicaciones ópticas; Radio; Underwater optical wireless communication; Scattering-induced fading; Óptica subacuática; Underwater optical turbulences; Comunicaciones ópticas